Essays on "the welfare state" - Titmuss, Richard Morris, 1907-1973 (Policy Press, 2018)
Richard Titmuss (1907-1973) was a pioneer in the field of social administration (now social policy) and this reissued classic contains a selection of his most famous writing on social issues. It covers subjects ranging from the position of women in society, changes in family life, and the social effects of industrialisation, to the problems of an ageing population, pensions, social security and taxation policy, and the development of the national health service. This collection contains one of Titmuss's most original contributions to the analysis of welfare policy - his reflections on 'The social division of welfare'. The book stands the test of time as representative of his thinking, and as an inspiration to those who wrestle with the complex issues of our welfare state.
Originally published in Great Britain in 1958 by George Allen and Unwin Ltd.
Keywords: Great Britain -- Social policy.; National health services -- Great Britain.; Welfare state.; Grande-Bretagne -- Politique sociale.; Services de santé -- Grande-Bretagne.; État providence.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Popular Culture.; National health services; Social policy; Welfare state; Great Britain; Electronic books.